(3GdOQ GdSfi aj efGbH GdTjN YHO GdZfi (B( (3GdfGHdSdi (B)s
(3ChdgG (B:s
(3MeOkG def HQgf HHGgQ bOQJg Ydi EKHGJ KHGJ hMOGfjJg s
(3BNQgG (B:s
(3GdCSQGQ GdCdhgjI MJi jUjO cGedkG ecedkG hCgdG ehgdG hgPG gh GdebUhO ef GdTjN GdcGed GfJgi eG hLO eLehYG ef cdGe GdTjN YHO GdZfi s
(3HgG fXcGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs